MODERN AND EFFECTIVE TECHNIQUES IN TEACHING VOCABULARY - Abdujalilova Feruza Milimamatovna (Innovate Conferences, 2025)
Vocabulary acquisition is a fundamental aspect of language learning, directly impacting reading comprehension, speaking, writing, and overall communicative competence. Traditional methods, relying heavily on rote memorization, have proven insufficient for fostering deep understanding and productive use of language. Modern pedagogical approaches integrate cognitive theories, communicative practices, digital tools, and multimodal strategies to enhance vocabulary acquisition. This paper reviews contemporary techniques, analyzes their theoretical foundations, and evaluates their effectiveness in classroom applications. Practical recommendations for language instructors are provided.
Keywords: Vocabulary teaching, language acquisition, digital tools, task-based learning, multimodal pedagogy, context-based learning.